2018
DOI: 10.1039/c8fd00036k
|View full text |Cite
|
Sign up to set email alerts
|

Towards the systematic crystallisation of molecular ionic cocrystals: insights from computed crystal form landscapes

Abstract: The underlying molecular and crystal properties affecting the crystallisation of ionic cocrystals (ICCs) with the general formula A-B+N (A- = anion, B+ = cation and N = neutral acid molecule; 1 : 1 : 1 stoichiometry) are reported for a limited set of known crystal structures determined following the cocrystallisation of either 4-aminopyridine (which forms salts) or 4-dimethylaminopyridine (which forms salts and ICCs) with the same set of monoprotic acids with a single hydroxy or halogen substitution at the ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 113 publications
2
28
0
Order By: Relevance
“…Comparison of the Kitaigorodsky packing coefficients (Ck ) of the molecular ICCs in our series with the packing coefficients of their respective molecular salts as reported in the CSD (see Table S3 in the Supporting Information for refcodes) show that only 5 , 6 , and 7 ‐ II display >1 % improvement (Table ) in Ck upon switching from the salt to the ICC. The finding that 2 – 4 show little or no change (Table ) in the packing efficiency of the species in the crystal as we switch from the binary salt to the ternary ICC is consistent with previous observations that poor crystal packing of salt ions is not a satisfactory explanation for rationalizing ICC formation. CSP studies (rigid molecular conformations) on the set of ICCs with previously reported crystal structures ( 3 – 6 and 7 ‐ I ) have shown (see Tables S6–S10) that all experimentally determined solid forms could be predicted within an energy range of 20 kJ mol −1 with respect to the global minimum (GM) structure.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Comparison of the Kitaigorodsky packing coefficients (Ck ) of the molecular ICCs in our series with the packing coefficients of their respective molecular salts as reported in the CSD (see Table S3 in the Supporting Information for refcodes) show that only 5 , 6 , and 7 ‐ II display >1 % improvement (Table ) in Ck upon switching from the salt to the ICC. The finding that 2 – 4 show little or no change (Table ) in the packing efficiency of the species in the crystal as we switch from the binary salt to the ternary ICC is consistent with previous observations that poor crystal packing of salt ions is not a satisfactory explanation for rationalizing ICC formation. CSP studies (rigid molecular conformations) on the set of ICCs with previously reported crystal structures ( 3 – 6 and 7 ‐ I ) have shown (see Tables S6–S10) that all experimentally determined solid forms could be predicted within an energy range of 20 kJ mol −1 with respect to the global minimum (GM) structure.…”
Section: Resultssupporting
confidence: 92%
“…We use the predicted crystal form landscapes (CFLs) to assess the preferred packing modes of ternary molecular ICCs and the degree to which CSP methods can guide the selection of ICCs in crystallization screens. We also test the hypothesis that the crystallization of ternary molecular ICCs is under thermodynamic control, and that the use of dispersion‐corrected density functional theory (DFT‐D) energies is diagnostic enough to guide the experimental discovery of ternary molecular ICCs.…”
Section: Introductionmentioning
confidence: 99%
“…One route to modified properties is the formation of multicomponent complexes, where the introduction of a second molecule into the crystal lattice can facilitate the engineering of solid-state forms with significantly different properties. [16][17][18] In this work, we sought to develop switchable materials by creating and switching between neutral cocrystals and ionic salts. In cocrystals, both components are formally neutral and typically interact through designable intermolecular interactions such as hydrogen or halogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Charge-assisted hydrogen bonds have definite scopes in the synthesis of non-covalent assemblies. [20][21][22][23][24] The electrostatic interactions in the noncovalent self-assemblies of inorganic complexes are common. [25][26][27][28] Among many examples of organic salts forming cocrystals the salts of active pharmaceutical ingredients, [25] carboxylic acid, [20][21][22][23][24] quaternary ammonium [29] and heterocycle containing oximes [30] are well studied.…”
Section: Introductionmentioning
confidence: 99%
“…[26] A mono-deprotonated dicarboxylic acid also may form cocrystal (BÀ H) + (B)(AH) À (Where B is a nitrogen based compound and AH is mono-anion of a dicarboxylic acid). [20][21][22][23][24] Some unsymmetrical dicarboxylic acids undergo preferential deprotonation [31] and certain acids form monodeprotonated salt. [32] A zwitterion has different complementarity for hydrogen bond than the conventional neutral form the changes in the hydrogen bonding patterns due to change in the ability to interact differently.…”
Section: Introductionmentioning
confidence: 99%